2013
DOI: 10.1089/aid.2012.0321
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Non-AIDS-Defining and Non-Virus-Related Cancers Among HIV-Infected Patients in the Combined Antiretroviral Therapy Era

Abstract: The risk of cancer is substantially increased in HIV-infected patients. However, little is known about non-AIDS-defining cancers (NADCs) without an infectious etiology. A total of 5,090 HIV-infected patients registered in the Local Health Authority (LHA) of Brescia and receiving primary care at our clinic were included in a retrospective (1999-2009) analysis. The cancer diagnoses were obtained through a record-linkage procedure between our database and the LHA general database and population-based Cancer Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
5
23
0
1
Order By: Relevance
“…The significant decreasing trend we observed in the HIV+ non-virus-NADC IR was consistent with findings from the HIV Outpatient Study [24], but inconsistent with results from northern Italy, where a borderline significant increasing trend was observed [25] and from Kaiser, where no trend was observed, either in the HIV+ IR or in the IRR [23]. The decreasing non-virus-NADC IRR trend that we observed, which took the decreasing uninfected non-virus-NADC IR trend into account, was only marginally significant.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The significant decreasing trend we observed in the HIV+ non-virus-NADC IR was consistent with findings from the HIV Outpatient Study [24], but inconsistent with results from northern Italy, where a borderline significant increasing trend was observed [25] and from Kaiser, where no trend was observed, either in the HIV+ IR or in the IRR [23]. The decreasing non-virus-NADC IRR trend that we observed, which took the decreasing uninfected non-virus-NADC IR trend into account, was only marginally significant.…”
Section: Discussionsupporting
confidence: 66%
“…Studies of adjusted IR time trends that classified NADC into broad groupings have produced inconsistent results [20, 2325]. Evidence supports decreasing trends for lung cancer and Hodgkin lymphoma and an increasing trend for liver cancer, but results for anal cancer have been inconsistent; many nonsignificant trends for specific NADC have been observed, perhaps due to insufficient statistical power [11, 1619, 2123, 26].…”
Section: Introductionmentioning
confidence: 99%
“…The genotoxic evaluation of antiretroviral drugs, including raltegravir, might be considered due to the high frequency of cancer in patients with AIDS [33]. …”
Section: Resultsmentioning
confidence: 99%
“…The effect of cART on cancer incidence is likely to be heterogeneous across cancer types. While some studies show no decreased risk of NADM as a whole for patients on cART 139,141,143 , a few large studies have identified HIV viremia as an independent risk factor for cervical cancer and anal cancer 149,151,152 , while others have found time on cART (or controlled HIV viremia) associated with decreased risk of certain non-virally associated NADM (largely lung cancer) 153 , as well as classical Hodgkin lymphoma 147 and anal cancer 152 . Differences between studies may depend in part on the definition of HIV viremia, with percent time with undetectable HIV a more sensitive measure of cART effect than single measurements of HIV viremia.…”
Section: Cancer Prevention Interventionsmentioning
confidence: 99%